A Second Chance for First Impressions? Exploring the Context-(In)Dependent Updating of Implicit Evaluations. (April 2017) - Brannon, Skylar M.; Gawronski, Bertram
Research on implicit evaluation has yielded mixed results, with some studies suggesting that implicit evaluations are relatively resistant to change and others showing that implicit evaluations can change rapidly in response to new information. To reconcile these findings, it has been suggested that changes in implicit evaluations can be limited to the context in which counterattitudinal information was acquired. The current research expands on evidence for such context-dependent changes by investigating whether two cases of rapid change—updating caused by a reinterpretation of earlier information and by exposure to diagnostic information—generalize across contexts or, instead, are limited to the context in which the qualifying information was acquired. Two experiments found that both reinterpretation of earlier information and diagnostic counterattitudinal information led to changes in implicit evaluations that generalized across contexts. Implications for the malleability of implicit evaluations and context-dependent changes in implicit evaluations are discussed.